Cartilage: Multiscale Structure and Biomechanical Properties. Issue 8 (2016) - Horkay, Ferenc; Basser, Peter J.; Hecht, Anne-Marie; Geissler, Erik
ABSTRACT: Cartilage is a load bearing tissue that has multiple biological functions. The major proteoglycan in cartilage is the bottlebrush shaped aggrecan whose complexes with hyaluronic acid provide the compressive resistance of cartilage. The negatively charged aggrecan-hyaluronic acid complexes generate an osmotic swelling pressure within the tissue, which is balanced by the collagen network. To better understand the function of cartilage at the tissue level, we study aggrecan assemblies using an array of microscopic and macroscopic techniques. The organization of aggrecan assemblies at the supramolecular level is probed by light scattering, small-angle neutron scattering and small-angle X-ray scattering. Osmotic and rheological measurements are used to investigate the macroscopic physical properties.